Inclusion needs in higher education in Mexico, from the students voice with visual disability - Wong, Karime Velázque (2023)
This research has as objective identify the inclusion barriers experienced by students with visual disabilities (VD) in higher education in Mexico. A qualitative method was used, through in-depth interviews to explore the perspectives and ideas of the students, as a necessary source of information that contributes to the understanding and generation of more inclusive processes in higher education (HE). Ten students from various degrees and semesters from eight universities in Mexico participated. From de data analyzed, the responses were organized by themes focused on investigating the educational background and inclusion barriers existing in HE and how the students with visual disabilities face them. The results suggest to an improvement in the infrastructure for greater accessibility and mobility in common spaces of social interaction, greater typhlotechnological and typhogenic support to the learning access, as well as teacher training and teacher qualification in teaching methodologies, reasonable adjustments and diversification of content. It concludes with the reconsideration of the aspects that difficult the construction of knowledge and learning of students with VD and that are essential for their inclusion in higher education institutions.